ANALYSIS OF NEEDS FOR DEVELOPMENT OF BASIC CONCEPT SOCIAL STUDIES TEACHING MATERIALS IN PRIMARY SCHOOL TEACHER EDUCATION COLLEGE STUDENTS - Rofiq, Muhammad Aunur; Nurwulandari, Ika (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
This study aims to analyze the students' needs for teaching materials in the basic concepts of social studies at STKIP Muhammadiyah Blora. Social studies basic concept courses are subjects that must be implemented by first semester students of the PGSD STKIP Muhammadiyah Blora Study Program. Currently the teaching materials used are simple teaching materials made by lecturers without paying attention to student needs. This study uses descriptive qualitative data analysis, namely analyzing the results of observations, interviews and user questionnaires about the basic concepts of social studies teaching material needs. The research was conducted at the PGSD STKIP Muhammadiyah Blora Study Program. The subjects of this study were the first semester students with a total of 47 students, Primary School Teacher Education Study Program, Basic Concept of Social Sciences courses. The results of data collection indicate that the teaching materials that need to be developed in the Basic Concepts of Social Studies course for PGSD students are textbooks in the form of modules. The development of teaching materials is based on the needs of students, namely on aspects of content / material, aspects of the feasibility of presenting teaching materials, and aspects of language feasibility.